2016
DOI: 10.1515/afmnai-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent Perioperative Hypothermia: A Literature Review of an Old Overlooked Problem

Abstract: Inadvertent perioperative hypothermia is a common anesthesia-related complication in patients undergoing surgery. This could possibly lead to several clinical consequences, which adversely affect the surgery outcome, particularly in high risk patient. The combination of anesthetic drugs and cold operating room environment are among the most common predisposing factors of perioperative hypothermia. The aim of this comprehensive literature review is to describe the importance, monitoring techniques, potential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Contradictory to these results, in our study, a higher stage of shivering happened for the female; this may have happened because of the type of surgeries in this study. A few researchers have found that less use of opiates can cause more shivering, as well as we know that pain threshold is higher in women and indeed BIS monitor would show a less score for a woman suffering from a pain compare to a man in the same situation [7], [9]. It has been previously shown that patients who underwent anaesthesia with Pentothal experience a higher incidence of postoperative shivering compare to propofol [2], [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contradictory to these results, in our study, a higher stage of shivering happened for the female; this may have happened because of the type of surgeries in this study. A few researchers have found that less use of opiates can cause more shivering, as well as we know that pain threshold is higher in women and indeed BIS monitor would show a less score for a woman suffering from a pain compare to a man in the same situation [7], [9]. It has been previously shown that patients who underwent anaesthesia with Pentothal experience a higher incidence of postoperative shivering compare to propofol [2], [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, they are less efficient than certain drugs such as tramadol, dexamethasone, pethidine, clonidine and physostigmine [6], [7], [8]. Pethidine is the most prevalent drug for managing postoperative shivering [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of cold liquids exacerbates hypothermia ( 5 , 6 ). Persistent hypothermia can lead to complications such as postoperative shivering, coagulopathy, decreased immunity, cardiac morbidity ( 7 ), postsurgical wound infection, impaired wound healing, prolonged recovery from anesthesia and prolonged hospital stay ( 6 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing free-flap microvascular surgery are particularly susceptible to IPH complications such as complete flap failure, surgical site infection, delayed wound healing, coagulopathies, dysrhythmias, myocardial events, and even death. [5][6][7][8] A comprehensive clinical review by Berrios-Torres et al 9 did not identify any randomized controlled trials that evaluated strategies to prevent surgical site infection associated with IPH but did call upon observational evidence suggesting that active warming measures may be effective in preventing surgical site infection. In both retrospective studies and randomized controlled trials, actively warmed patients experienced less blood loss and of care to meet national quality improvement goals to reduce perioperative complications and improve postoperative outcomes.…”
mentioning
confidence: 99%